(3JWhjQ eYGjjQ GdJbjje GdPGJj GdJTGQcj hELQGAGJg HMSH eHGOiA (B"(3eLJeY GdJYode Gdegfj(B":(3fehPL dJLPjQ GdJLQHI aj hGbY GdeOQSI GddHfGfqjIs - (3QRb Gddg, OdGd SejQs ((3HjQhJs (3GdLGeYI GddHfGfjI (B- (3GdeYgO GdYGdj ddOcJhQGg aj GdBOGH hGdYdhe GdEfSGfnqjIs, 2015)
(3jQJcR gPG GdHMK Ydi GdbfGYI Cnqfg CeGe GdJMOpqjGJ GdeWQhMI Ydi GdeOQSI aj GdYGde GdYQHj YehkeG, haj dHfGf NUhkUG, dG HnqO ef WQM ehVhY GdLhOI GdJQHhnqjI hCSGdjH Jbjje GdeOQSI hJWhjQgG, WQkMG YdekqjG, jMGcj aQGOI GdeLJeY GdJQHhj GddHfGfj(B. (3cPdc JQJcR Ydi Cnqf JMbjb GdLhOI UGQ WQjkbG CSGSkqjG jecf GYJeGOg aj GdeOGQS GddHfGfnqjI, dEMOGK JZjjQ fhYj aj COGFgG GdJQHhj hGdJYdjej hGdEOGQj, ehGcHI deJWpqdHGJ GdYUQ, hCShI HGdHdOGf GdeJbpqOeI(B. (3hYdjg, gOa gPG GdHMK Edi HfGA fehPL ddJbjje, eSJhMi ef eHGOF fXQnqjI (B"(3GdeLJeY GdJYoqdej(B"(3, hef eaghe GdbjGOI GdJYdjenqjI, eLnqPQ aj GdSjGb GddHfGfj, hefHKb ef MGLGJ eOGQSg(B. (3dJMbjb gPG GdgOa, Jnqe(B: (3ChdkG(B: (3ESJfHGW dGFMI eYGjjQ eHOFnqjI ef eQGLYI GdCOHnqjGJ, hJMOjO ecpqhfGJ eHOFnqjI eSJhMGI ef GdfXQnqjGJ hfJGFL GdCHMGK GdYGdenqjI ddeOQSI GdfGLMI GdeQJHWI HGdfehPL GdePchQ(B. (3KGfkjG(B: (3JLoqPQ GdeYGjjQ aj hGbY GdeOQSI GddHfGfnqjI, hJUeje COhGJ GdJbjje GdPGJj, hJMOjO BdjGJg, hJfXje ELQGAGJg, EfWdkbG ef gPg GdGFMI GdeJLpqPQI aj GdhGbY GdeMqdj(B. (3YeO GdHMK Edi JWHjb fehPL GdJbjje aj eOQSI JLQjHnqjI, hGSJNdU(B! (3GdfJGFL hGdJhUjGJ GdJj JSge aj JWhjQ COGA GdeOQSI hJMhjd eLJeYgG Edi HjFI JYoqdenqjI(B. (3jcJSH GdHMK CgenqjJg dchfg jJfGhd ehVhY EONGd KbGaI GdJbjje GdPGJj hegGQGJg Edi GdeOQSI GddHfGfnqjI, hJMOjO CgOGa eYnqjfI ddJWhjQ eHfnqjI Ydi gPG GdJbjje(B. (3hjYJeO ebGQHI GdJbjje GdPGJj GdJTGQcj djLpqPQ GdeYGjjQ GdYGdenqjI, GdeSJhMGI ef NHQGJ GdeDnqSSGJ GdJQHhnqjI GdCeQjcnqjI GdfGLMI, JMOjkqOG ef eHGOF (B"(3eLJeY GdJYoqde Gdegfj(B"(3, heYGjjQ bjGOJg GdJYdjenqjI, aj GdhGbY GdeMqdj GddHfGfj(B. (3dPdc GnqJHY GdHMK fehPLG JbjjekjG YeO Edi ETQGc CYVGA GdeLJeY GdeOQSj aj YednqjI GdJbjje, ef LgI, hJMOjO JWoqdYGJge ef LgI CNQi, hGdGSJaGOI ef NHQGJge cLRA CSGSj aj efgLnqjI GdHMK hGdJbjje(B. (3ceG CaSM aj GdeLGd CeGege dJMOjO GdecpqhfGJ, heUGOQ GdeYdheGJ, hHfGA COhGJ GdJbjje ef NdGdgG, acGfJ dge aQUI djdYHhG OhkQG aGYdkG aj YednqjI HfGA HQfGeL Jbjje NGU HeLJeYge GdeOQSj, hef Knqe JWHjbg(B. (3bO GSJOYi hVY NWI GdJbjje gPg ELQGA MdbGJ HMK ELQGFj dLeY GdeYdheGJ GddGReI hGSJNOGegG dEYOGO GdeYGjjQ, hJMOjO eUGOQ GdeYdheGJ GdehGabI dcpqd eDpqTQ, hcPdc dHfGA COhGJ LeY GdeYdheGJ GdJj GSJNOeJ NdGd GdJbjje GdPGJj(B. (3GNJJeJ GdCWQhMI HeLehYI JhUjGJ eRO(B! (3hLI(B: (3CĎ(B) (3GQJHWJ GdeLehYI GdChdi efgG(B: (3ChdkG(B: (3HGdeeGQSjf dLgI JWhjQ GdCOGA GdJQHhj Ydi eSJhi eOGQS GdJLoqeY ccqd ef LgI, hYdi eSJhi GdeOQSI GdJLQjHnqjI ef LgI CNQi(B. (3KGfkjG(B: (3GQJHWJ HehVhY JWHjb GdJbjje GdPGJj GdJTGQcj hCKQg Ydi GdYednqjI GdJWhjQnqjI(B. (3HĎ(B) (3GQJHWJ eLehYI GdJhUjGJ GdKGfjI HGdHGMKjfs
(3GdfhY (B: (3CWQhMIs
Keywords: Education de qualitâe; Evaluation Institutionnelle; Institutional assessment; Quality Education; (3GdJbjje GdeDSSjs; (3LhOI GdJYdjes